Strategies to improve care for older adults who present to the emergency department: a systematic review - Luke Testa; Lieke Richardson; Colleen Cheek; Theresa Hensel; Elizabeth Austin; Mariam Safi; Natália Ransolin; Ann Carrigan; Janet C. Long; Karen Hutchinson; Magali Goirand; Mia Bierbaum; et al. (2024)
Background: The aim of this systematic review was to examine the relationship between strategies to improve care delivery for older adults in ED and evaluation measures of patient outcomes, patient experience, staff experience, and system performance. Methods: A systematic review of English language studies published since inception to December 2022, available from CINAHL, Embase, Medline, and Scopus was conducted. Studies were reviewed by pairs of independent reviewers and included if they met the following criteria: participant mean age of ≥ 65 years; ED setting or directly influenced provision of care in the ED; reported on improvement interventions and strategies; reported patient outcomes, patient experience, staff experience, or system performance. The methodological quality of the studies was assessed by pairs of independent reviewers using The Joanna Briggs Institute critical appraisal tools. Data were synthesised using a hermeneutic approach. Results: Seventy-six studies were included in the review, incorporating strategies for comprehensive assessment and multi-faceted care (n = 32), targeted care such as management of falls risk, functional decline, or pain management (n = 27), medication safety (n = 5), and trauma care (n = 12). We found a misalignment between comprehensive care delivered in ED for older adults and ED performance measures oriented to rapid assessment and referral. Eight (10.4%) studies reported patient experience and five (6.5%) reported staff experience. Conclusion: It is crucial that future strategies to improve care delivery in ED align the needs of older adults with the purpose of the ED system to ensure sustainable improvement effort and critical functioning of the ED as an interdependent component of the health system. Staff and patient input at the design stage may advance prioritisation of higher-impact interventions aligned with the pace of change and illuminate experience measures. More consistent reporting of interventions would inform important contextual factors and allow for replication.